Precision exosome engineering for enhanced wound healing and scar revision - Chuanqi Liu; Chen Cheng; Kun Cheng; Allen S. Gao; Qingfeng Li; Anthony Atala; Yuanyuan Zhang (Journal of Translational Medicine)
Abstract The dysfunction of wound-healing processes can result in chronic non-healing wounds and pathological scar formation. Current treatment options often fall short, necessitating innovative approaches. Exosomes, extracellular vesicles secreted by various cells, have emerged as promising therapeutic agents serving as an intercellular communication system. By engineering exosomes, their cargo and surface properties can be tailored to enhance therapeutic efficacy and specificity. Engineered exosomes (eExo) are emerging as a favorable tool for treating non-healing wounds and pathological scars. In this review, we delve into the underlying mechanisms of non-healing wounds and pathological scars, outline the current state of engineering strategies, and explore the clinical potential of eExo based on preclinical and clinical studies. In addition, we address the current challenges and future research directions, including standardization, safety and efficacy assessments, and potential immune responses. In conclusion, eExo hold great promise as a novel therapeutic approach for non-healing wounds and non-healing wounds and pathological scars. Further research and clinical trials are warranted to translate preclinical findings into effective clinical treatments.